THE CORRELATION BETWEEN STUDENTS ENGAGEMENT AND STUDENTS ENGLISH ACHIEVEMENT - Rizaldi, Rizki (Universitas Mahaputra Muhammad Yamin, 2024)
This research investigates the correlation between student engagement and learning achievement in English among ninth-grade students at UPT SMPN 3 X Koto. Despite high engagement levels, low academic performance in English has been observed, suggesting varying combinations of behavioral, emotional, and cognitive engagement. The study aims to explore how different dimensions of engagement impact learning outcomes in the context of English language learning. Utilizing a correlational design with total sampling, data was collected through a validated student engagement questionnaire and standardized English proficiency tests to measure learning achievement. The Pearson Product Moment Correlation Coefficient was employed for data analysis using SPSS 25. The findings reveal a statistically significant positive correlation between emotional engagement and learning achievement, emphasizing the crucial role of emotional factors in predicting academic success. The results highlight the importance of fostering emotional engagement strategies to enhance English language learning outcomes among ninth-grade students.